Asmara, an urban history (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2014)
This publication defines the culmination of a doctoral thesis, focusing on the urban history and development of the city of Asmara (Eritrea). The thesis had been written with the aim of tracing the history of the urban evolution of the city of Asmara in order to identify its morphology which had beengenerated by both planned and unplanned urban spatial development. The first part of the book discusses the urban development knowledge of Asmara before 1941, in a historical and logical discourse, within an analytical framework comprising the following components: population, geography and history of the place. However, the main focus of this study is the second part which connects the colonial development of the city with the contemporary form, from 1941 to 2005. Asmara was generatedat the beginning of 1500 A.D.,emerging from the union of four villages that was collectively known as ArbatÃ¨ Asmera and the city started to develop as an urbanized settlement since the end of the nineteenth century A.D.From about the year 1893 the bulk of the city developed along the infrastructure and urban planning principles of the Italian colony administration. During the said administration urban planning in Asmara had been closely related to that of Italian cities and to those urban features and principles of Western urban planning. At the end of Italian colonialism in April â€˜41 Eritrea fell under British administration which reigned until 1952, during which time there were no processes of any urban planning despite the city continuing to grow organically. This situation persisted even during the years of Federation (1952-1962) and annexation (1962-91) in Ethiopia. In order to understand the development of an organic urban plan of the city during the recent past decades, reference must be made to the beginning of the 70s during which time a new Master Plan for Asmara was conceptualised and developed by the Siena-based architect, Arturo MezzÃ¨dimi. The Town Plan of the MezzÃ¨dimi Firm therefore represented the last comprehensive plan for the city of Asmara. The thesis concludes by establishing the origins and precursors to the contemporary city of Asmara. It was found that urban development planning was stagnant during the subsequent three decades following the 70s and any new planning would only start to materialise in the year2005, primarily through the initiatives of the Government of Eritrea and international consulting firms. This realised the development of â€œThe Strategic Urban Development Plan, and the Identification of Priority Projectsâ€documentwhich was accompanied by a Strategic Plan and an outline of Urban Planning Regulations. These documents were sourced and their respective contents synthesised in order toinform a true general plan of the entire Greater Asmara Area thereby representing the new beginning of the city. The historic links in the evolution and development of the city of Asmara, in Eritrea, is thereby established.